Characterization of the oxidative metabolism of erythrocytes in patients with community-acquired pneumonia - L. A. Demidchik; L. E. Muravlyova; V. B. Molotov-Luchanskiy; R. E. Bakirova; D. A. Kluyev; E. A. Kolesnikova (Acta Biomedica Scientifica, 2016)
Free radical oxidation plays an important role in the development and exacerbation of the pathological process. Oxidative stress causes a disturbance of the rheological properties of red blood cells and modification of their membrane. Activation of processes of peroxidation of lipids disturbs the integrity of the erythrocyte membrane. In community-acquired pneumonia the study of oxidative metabolism of red blood cells, especially the oxidative modification of their proteins, dedicated to a limited number of studies. Oxidative modification of hemoglobin dissipate a key role in the development of inflammation induced by hypoxia. The aim of the research was to study indicators of oxidative stress, the content of oxidized modified proteins in the red blood cells and the permeability of their membranes to low-molecular-weight hydrophilic substances in patients with community-acquired pneumonia. The object of the study were the erythrocytes of blood of 33 patients with community-acquired pneumonia and 19 practically healthy persons of young and middle age from 27 to 42 years. Evidence of oxidative processes in red blood cells was a significant increase of the oxidized-modified proteins (carbonyl derivatives) in erythrocytes. The increase in the content of membrane-bound hemoglobin may also be due to the high level of lipid peroxidation in erythrocyte membranes. The results of the study showed the presence of intracellular oxidative stress in erythrocytes of patients with community-acquired pneumonia, which leads to damage to their membranes and release of hemoglobin into the blood plasma.